Curcumin versus placebo in benign prostatic hyperplasia: a systematic review and meta-analysis - Diogo Souto Santana; Breno Cordeiro Porto; Rafael Baldissera Cardoso; Guilherme Melchior Maia Lopes; Luiz Guilherme Serrão Gimenez; Carlo Camargo Passerotti; Ronaldo Maia; Fernando Gonçalves Almeida; Rodrigo Afonso da Silva Sardenberg; José Arnaldo Shiomi da Cruz (European Journal of Clinical Pharmacology, 2026)
Background Benign prostatic hyperplasia (BPH) is a highly prevalent condition among aging men and a major cause of lower urinary tract symptoms (LUTS). Although α1-adrenoceptor blockers and 5-alpha-reductase inhibitors remain the cornerstone of treatment, their long-term use is frequently limited by adverse effects and suboptimal symptom control. Growing experimental and clinical evidence suggests that chronic prostatic inflammation plays a central role in BPH progression, raising interest in anti-inflammatory compounds such as curcumin. However, the clinical effectiveness of curcumin in BPH remains poorly defined. Methods We conducted a systematic review and meta-analysis of randomized and nonrandomized comparative studies evaluating curcumin versus placebo in men with BPH receiving α-blockers and/or 5-alpha-reductase inhibitors. Searches were performed in PubMed, Embase, and Cochrane CENTRAL. The primary outcome was change in International Prostate Symptom Score (IPSS). Secondary outcomes included prostate-specific antigen (PSA), prostate volume (PV), post-void residual volume (PVR), and maximum urinary flow rate (Q-max). Pooled analyses were performed using a random-effects model. Results Six studies involving 697 patients met the inclusion criteria. Compared with placebo, curcumin was associated with a significant improvement in IPSS (MD − 4.11; p = 0.0009), accompanied by reductions in PSA (MD − 0.52 ng/mL), PV (MD − 3.78 mL), and PVR (MD -2.38 mL), as well as an increase in Q-max (MD 2.09 mL/s). Subgroup analyses suggested greater symptomatic benefit among patients receiving α-blockers alone compared with those on combined α-blocker and 5-alpha-reductase inhibitor therapy. Substantial heterogeneity was observed across outcomes. Conclusion Curcumin supplementation was associated with significant improvement in LUTS and functional parameters in men with BPH. Although these findings support a potential adjunctive role for curcumin, the available evidence is limited by heterogeneity and study design variability. Well-designed, large-scale randomized trials are warranted to define its clinical utility, optimal formulation, and long-term effects.